Pro Visual C++ 2005 for Developers: Featuring C++/CLI - C.Wills, Dean (Apress, 2012)
C++/CLI is a bit of amisnomer. It is a set of extensions that allow C++ to expose the power of the Common Language Infrastructure (CLI). Really, it portends the future of C++. There is no reason that C++/CLI features, such as events and properties, could not be a part of standard C++.